Functional role of mucosal‐associated invariant T cells in HIV infection. Issue 2 (2nd June 2016) - Saeidi, Alireza; Ellegård, Rada; Yong, Yean K.; Tan, Hong Y; Velu, Vijayakumar; Ussher, James E.; Larsson, Marie; Shankar, Esaki M.
Abstract : Review on mechanisms associated with functional loss of MAIT cells in HIV infection. Abstract : MAIT cells represent an evolutionarily conserved, MR1‐restricted, innate‐like cell subset that express high levels of CD161; have a canonical semi‐invariant TCR iVα7.2; and may have an important role in mucosal immunity against various bacterial and fungal pathogens. Mature MAIT cells are CD161 hi PLZF hi IL‐18Rα + iVα7.2 + γδ‐CD3 + CD8 + T cells and occur in the peripheral blood, liver, and mucosa of humans. MAIT cells are activated by a metabolic precursor of riboflavin synthesis presented by MR1 and, therefore, respond to many bacteria and some fungi. Despite their broad antibacterial properties, their functional role in persistent viral infections is poorly understood. Although there is an increasing line of evidence portraying the depletion of MAIT cells in HIV disease, the magnitude and the potential mechanisms underlying such depletion remain unclear. Recent studies suggest that MAIT cells are vulnerable to immune exhaustion as a consequence of HIV and hepatitis C virus infections and HIV/tuberculosis coinfections. HIV infection also appears to cause functional depletion of MAIT cells resulting from abnormal expression of T‐bet and EOMES, and effective ART is unable to completely salvage functional MAIT cell loss. Depletion and exhaustion of peripheral MAIT cells may affect mucosal immunity and could increase susceptibility to opportunistic infections during HIV infection. Here, we review some of the important mechanisms associated with depletion and functional loss of MAIT cells and also suggest potential immunotherapeutic strategies to restore MAIT cell functions, including the use of IL‐7 to restore effector functions in HIV disease.